2016
DOI: 10.1177/2047487316652975
|View full text |Cite
|
Sign up to set email alerts
|

Screening for obstructive sleep apnoea in cardiac rehabilitation: A position statement from the Australian Centre for Heart Health and the Australian Cardiovascular Health and Rehabilitation Association

Abstract: Obstructive sleep apnoea is highly prevalent in acute coronary syndrome patients eligible for enrolment in cardiac rehabilitation programmes. This condition is an independent predictor of increased morbidity and comorbid conditions in the general population and can lead to an increase in major adverse cardiac events such as revascularization, heart failure and hospital readmission in cardiac patients. There is convincing evidence that treatments such as continuous positive airway pressure or mandibular advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 71 publications
(76 reference statements)
1
15
0
1
Order By: Relevance
“…In our sample, 40.5% of patients had a high OSA risk, a prevalence similar to previous studies showing that close to a half of patients with ACS have moderate or severe OSA (apnea-hypopnea index ≥15) [ 55 ]. Also comparable to a previous study showing that 37.3% of hospitalized patients with ACS have clinically relevant insomnia symptoms [ 56 ], 27.4% of our patients were poor sleepers.…”
Section: Discussionsupporting
confidence: 86%
“…In our sample, 40.5% of patients had a high OSA risk, a prevalence similar to previous studies showing that close to a half of patients with ACS have moderate or severe OSA (apnea-hypopnea index ≥15) [ 55 ]. Also comparable to a previous study showing that 37.3% of hospitalized patients with ACS have clinically relevant insomnia symptoms [ 56 ], 27.4% of our patients were poor sleepers.…”
Section: Discussionsupporting
confidence: 86%
“…Нарушение дыхания во сне в форме синдрома обструктивного апноэ во сне (ОАС), или апноэ центрального происхождения, -важный фактор сердечно-сосудистого риска, который характеризуется повторяющимися эпизодами коллапса верхних дыхательных путей во время сна. В целом 53% пациентов, попадающих в программы КР, имеют либо ОАС, либо высокий риск развития ОАС [35]. Пациенты с нарушением дыхания во сне имеют значительно больший объем инфарктной зоны миокарда и менее выраженное уменьшение размера инфаркта в течение 3 мес после острого инфаркта миокарда.…”
Section: нарушение дыхания во снеunclassified
“…Secondary analysis of CR patient data has indicated that sleep disorders such as OSA have the potential to hamper rehabilitation efforts by affecting treatment adherence, self-efficacy and psychological wellbeing [18]. Until recently [19,20], OSA has rarely been mentioned as a risk factor to be managed among cardiac patients. The widespread absence of OSA as a target for screening in CR may be due to the relative paucity of prevalence data in this population.…”
Section: Introductionmentioning
confidence: 99%